Evidence-based clinical practice guidelines for communication strategies to support end-of-life decision-making by persons with Aphasia - Tonsing, Kerstin Monika (University of Pretoria, 2025)
Thesis (PhD (Augmentative and Alternative Communication))--University of Pretoria, 2025.